THE EFFECT OF ADDING HARD & SOFT LINERS ON SHEAR BOND OF CAD-CAM 3D PRINTED & CONVECTIONAL HEAT CURED DENTURE BASE MATERIALS BEFORE & AFTER THERMAL-CYCLING (CAHIERS MAGELLANES-NS, 2024)
: An in vitro study to compare the shear bond of denture bases fabricated with 2 different techniques (CAD-CAM 3D Printed & Conventional Heat-Cured), After Relining with Hard & Soft liners & After Thermal-Cycling.Material and Methods: The minimum sample size was calculated by using a software program (3D Builder, Microsoft, U.S.A). The denture base resin was designed as a cylindrical shape with a diameter of 20.0 mm and a height of 14.0 mm as a standard tessellation language (STL) file, connected to another cylindrical shape with a diameter of 4 mm and a height of 4 mm cylinder and then an SLA type 3D-printer (Asiga, Australia) was used to print the specimens of 3D. The layer thickness (100 µm) was set, supports were placed opposite to the testing side, and printed in 0°. After the supports were removed, the specimens were post-polymerized in glycerin at 80°C for 20 minutes to follow the manufacturer’s instructions. The underside of the specimens was reversed and light-cured in a post-curing machine for 20 minutes in the same manner. To make the bottom surfaces parallel and flat to each other, they were polished with an automatic polishing device (LaboPol-5; Struers, Copenhagen, Denmark). Then, the specimens were cleaned using an ultrasonic cleaner (SD-120H; Mujigae Co., Seoul, Korea) with distilled water for 20 minutes. For following ISO 10139-2, The specimens were stored in distilled water at 37°C for 24 hours. The models of the 3D printed denture base materials of shear bond test were used to produce the conventional heat cured specimens, The two parts of the flask were tightened to each other, they were pressed under a compression force of 13.8 kPa. (TISSIDental, Italy), The flask was kept in water at room temperature for 1 hour and the temperature is raised to 74℃ (165F) and maintained for 9 hours in the curing machine (Zung, China) The total specimens of shear bond test were 80 specimens, 20 of them were 3D printed denture base materials (Saremco Denture Base, Germany), 20 of them were conventional heat cured denture base materials (Procryla, Germany), 20 specimens of 3D printed were relined, Specimens from (1-10) were relined with hard relining material (PMMA), while specimens from (11-20) were relined with soft resilient denture liner (Super Soft, USA). 20 specimens of conventional denture base were relined. Specimens from (1-10) were relined with hard relining material (PMMA), while specimens from (11-20) were relined with soft resilient denture liner (Super Soft, USA), then shear bond strength test was calculated after relining, then additional number of samples 40 were relined, they were thermal cycled, The specimens were kept for 24 hours in an incubator at 37℃ and not thermocycled, then they were thermocycled for a total of 5000 cycles between 5 ℃ and 55 ℃ with a dwell time of 60 seconds and a transfer time of 30 seconds. subjected to 5,000 cycles of thermocycling (SD Mechatronik Thermocycler; SD Mechatronik GmbH, Westerham, Germany) & the shear bond strength test was calculated another time using A universal testing machine (TERCO, MT 3037, Sweeden).Results: (⸸): t-test (Two independent sample), (¥): Z=Mann-Whitney U were used when the specimens of CAD-CAM (3D printed) were relined with hard liner (PMMA) & then thermal cycled, there was a significant increase in shear bond strength (p<0.05). While when the specimens of 3D printed were relined with soft liner (SUPER SOFT) & then thermal cycled, there was no significant change (p>0.05). When the specimens of Conventional heat cured were relined with hard liner (PMMA) & then thermal cycled, there was no significant change (p>0.05). While when the Conventional heat cured were relined with soft liner (SUPER SOFT) & then thermal cycled, there was significant decrease after thermal cycling (p<0.05). £: F-test One Way ANOVA, Ӄ: Kruskal-Wallis H test, (a),(b),(c) multiple comparison by Duncan multiple range test for Parametric test, (1),(2),(3),(4) Rank for Not Parametric test, were used for Comparison Analysis of shear bond of 3D & conventional Denture Bases between 3DH (3D Hard), 3DS (3D Soft), CH (Conventional Hard), & CS (Conventional Soft) liners at Both Group after relining, there was Significant differences (p<0.05). Highest in conventional hard, lowest in 3D soft. While when the specimens of Conventional & CAD-CAM (3D printed) were compared After Thermal Cycling, there was also Significant differences (p<0.05). Highest in conventional hard, lowest in conventional soft.Conclusion: When the CAD-CAM 3D Printed denture Base relined with hard liner there was significant increase After Relining & Thermal-Cycling. But when relined with soft liner & thermal cycled there was no significant changes occurred. shear bond strength was estimated After Relining, (3DH, 3DS, CH &CS) liners from both Group, & Thermal-Cycling, there was significant differences, highest in Conventional hard, lowest in 3D soft.